LINGUISTIC AND EXTRALINGUISTIC FACTORS OF ACADEMIC TEXTS - Mukumov, Makhmud (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores how syntax, vocabulary, cultural context influence scientific style. It references researchers like Swales and Hyland, offering strategies for effective writing and highlighting the complexities of academic texts.